The ethical treatment of information from professional journalism in coverage of attacks on schools: a new perspective on the dissemination of information in the online environment (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
In recent years, episodes of school massacres have led traditional media outlets that also operate in the online environment to change their ethical stance in dealing with and disseminating information. The objective of this paper is to point out what these changes are and what are the possible ethical implications. The methodology used for data collection was the bibliographic and documentary review, in an exploratory research in a qualitative approach. It is concluded that changing the way of treating and disseminating information is important to discourage other aggressors in the future, not to make them "celebrities" and to avoid fake news about what happened.
Keywords: ethics; schools; Processing of Information